Effects of a rotating tube bundle on the hydrothermal performance for forced convection in a vented cavity with Ag-MgO/water hybrid and CNT-water nanofluids - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer, 2022)
In this study, effects of rotating tube bundle on the hydrothermal performance for the forced convection in a vented cavity are numerically studied with a mixture of Ag and MgO nanoparticles suspended in water, forming a hybrid nanofluid and CNT-water nanofluid. The finite volume method is used for the numerical simulations. The simulation study is performed for various values of Reynolds number (between 100 and 1000), rotational Reynolds number (between - 100 and 100), size (between 0.01H and 0.12H), vertical (between 0.3H and 0.65H) and horizontal locations (between 0.3H and 0.65H) of the cylinder in the tube bundle and nanoparticle volume fraction (between 0 and 0.02). An experimental correlation was used for the description of the Ag-MgO/water hybrid nanofluid. Results indicated that the rotational effects of the tube bundle contribute to the hydrothermal performance. The average Nusselt number enhancements are 8.95% and 40% when CNT-water is used for solid volume fraction of 0.02 at the highest speed, while these values are 31.5% and 37.7% for hybrid nanofluid. The pressure coefficients are higher for negative value of Re-omega and hybrid nanofluid. The size of the tube bundle is effective at the highest size, while the increment amount is 16.8% both for CNT-water and for hybrid nanofluids. The center location of the tube bundle resulted in heat transfer enhancement which is in the range of 11% and 18%. As the solid volume fraction of nanoparticles becomes higher, discrepancies between the average Nu values of CNT-water nanofluid and Ag-MgO/water hybrid nanofluid become higher which is also observed for the pressure coefficient. It is advantageous to use CNT particles since higher heat transfer coefficients with lower values of pressure coefficient are obtained.
Keywords: Rotating tube bundle; Finite volume method; CNT nanofluid; Hybrid nanofluid; Vented cavity